Deteksi PenularanPenyakit CVPD pada Jeruk Rough Lemon Menggunakan Inokulum dari Berbagai Jaringan Tanaman Sakit dengan Tingkat Gejala yang Berbeda - Marlina, Marlina; Hayati, Islah; Mapegau, Mapegau (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2022)
CVPD disease is an important disease in citrus plants. This disease can reduce the productivity of citrus plants. This study aimed to detect the transmission of CVPD disease by using inoculum sources from various diseased tissues. The experimental design used was a completely randomized design with a two-factor factorial pattern. The first factor was the level of symptoms of the inoculum source (partially symptomatic, and fully symptomatic), while the second factor was the diseased plant parts as a source of inoculum, namely: leaf tissue, middle leaf bone, woody twig tip, woody middle twig, middle twig without wood, woody roots, and root bark. Response data of diseased plants inoculated by grafting various diseased tissues were obtained through variables: incubation period, percentage of leaf chlorosis, and percentage of symptomatic branches. The results showed that the incubation period of CVPD disease, percentage of symptomatic branches, and percentage of leaf chlorosis on Rough Lemon citrus plants inoculated with CVPD pathogens from plants with overall symptoms was faster and the percentage was higher than those with partial symptoms of all types of diseased tissue, except the middle tissue of twigs and roots without wood. A faster incubation period was te